Work-Life Balance, Stres Kerja, dan Kinerja Karyawan: Peran Mediasi Kepuasan Kerja pada Mahasiswa - Muh Nur Alamsyah Ibrahim; Osly Usman (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to examine the effect of Work-Life Balance and Work Stress on Employee Performance, with Job Satisfaction serving as a mediating variable among working students enrolled in the Master's Program in Management at Universitas Negeri Jakarta. A quantitative research approach was employed using a survey method. Data were collected through questionnaires distributed to 50 respondents selected using a purposive sampling technique. The data were analyzed using Partial Least Squares-Structural Equation Modeling (PLS-SEM) with SmartPLS 4 software. The results indicate that Work-Life Balance has a positive and significant effect on both Employee Performance and Job Satisfaction, while Work Stress has a negative and significant effect on Employee Performance and Job Satisfaction. Furthermore, Job Satisfaction has a positive and significant effect on Employee Performance. The mediation analysis reveals that Job Satisfaction significantly mediates the relationships between Work-Life Balance and Employee Performance, as well as between Work Stress and Employee Performance. These findings suggest that maintaining a balance between work and personal life, along with effective work stress management, enhances job satisfaction, which subsequently improves employee performance. This study provides practical implications for organizations to develop policies that support work-life balance, effectively manage work stress, and improve job satisfaction to optimize employee performance, particularly for individuals who simultaneously fulfill the roles of employees and graduate students.